Passive design and performance evaluation of building using e-quest:a case study - Samanta, A.; Dutta, A.; Neogi, S. (Penerbit UKM, 2013)
There are many factors that drive the energy consumption and demand in high-rise commercial office buildings. Through a case study, this paper presents an approach to evaluate how different types of sunshields, building orientations, position of windows and wall window ratio (WWR) affect the energy consumption of a facility. e-Quest, an energy simulation software is used to simulate the energy performance of the facility. The simulation model is calibrated against the measured monthly electrical consumption. The subject facility is located in Kolkata, India. Calibrated simulation model of a building has been created using the real data gathered during energy audit to estimate the energy saving potential through the implementation of the passive building architectural designs by a simulation software e-Quest. Finally an optimum passive building design recommendation to reduce the building energy consumption is in this paper to assist the facility managers. The detailed energy simulation gives recommendation on window orientation, WWR and optimum shading design.